BPJS Patient’s Satisfaction Towards Waiting Time of Administrative and Pharmacy Services - Wardani, Silvia Intan; Guntari, Gusti Agung Sri (Babali Nursing Research, 2024)
Introduction: The waiting time for services is one of the aspects that is thought to affect patient satisfaction. In many hospitals, patients frequently complain about the length of the wait for services. The study aims to explore BPJS patients’ satisfaction with the waiting time of administrative and pharmacy services. Methods: The literature review was to examine the results of previous research in published articles. Articles were carried out via PubMed, Science Direct, and Google Scholar using the keywords using keyword were “BPJS patient’s satisfaction”, “administrative services”, and “waiting time pharmacy”. The inclusion criteria of this study were BPJS patients’ satisfaction, published articles in Bahasa or English, and full-text access. The study only focused on administrative services and waiting time pharmacy, all of the studies involved other conditions that were removed. Data were extracted and recorded using a table consisting of author names, years, methods, instruments, and findings, including factors related to and variable dimensions. Result: The findings of this study highlight several key factors influencing BPJS patients' satisfaction with waiting times for administrative and pharmacy services. Conclusion: BPJS patient satisfaction is influenced by multiple factors, including waiting times for administrative and pharmacy services, overutilization, patient expectations, communication, and perceived quality of service.